2009
DOI: 10.1089/mdr.2009.0008
|View full text |Cite
|
Sign up to set email alerts
|

23S rRNA Mutation A2074C Conferring High-Level Macrolide Resistance and Fitness Cost inCampylobacter jejuni

Abstract: To examine the development of macrolide resistance in Campylobacter jejuni and assess the fitness of the macrolide-resistant mutants, two macrolide-susceptible C. jejuni strains, American Type Culture Collection (ATCC) 33291 and H1, from different geographic areas were exposed to tylosin in vitro. Multiple mutant strains were obtained from the selection. Most of the high-level macrolide-resistant strains derived from the selection exhibited the A2074C transversion in all three copies of 23S rRNA and displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Third, a large number of genes involved in the heat shock response, motility, and energy metabolism were significantly downregulated in the macrolideresistant mutants, suggesting that the development of macrolide resistance in C. jejuni profoundly impacts Campylobacter physiology and may result in a growth burden and fitness cost. Indeed, several recent studies found that macrolide-resistant Campylobacter shows a significant fitness cost in vitro and in vivo and is outcompeted by susceptible Campylobacter in the chicken host in the absence of antibiotic selection pressure (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a large number of genes involved in the heat shock response, motility, and energy metabolism were significantly downregulated in the macrolideresistant mutants, suggesting that the development of macrolide resistance in C. jejuni profoundly impacts Campylobacter physiology and may result in a growth burden and fitness cost. Indeed, several recent studies found that macrolide-resistant Campylobacter shows a significant fitness cost in vitro and in vivo and is outcompeted by susceptible Campylobacter in the chicken host in the absence of antibiotic selection pressure (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the multiple-stepwise-selection approach could yield pleiotropic mutations, thus underestimating the importance of the CmeABC-overproducing mutants that also possessed ϳ200 up-or downregulated genes (including the upregulation of genes encoding an SMR pump [Cj1173] and two MFS pumps [CmeG and Cj0035c]), and some of these changes may affect physiology and metabolism (668). The latter offers an explanation regarding the growth burdens and fitness cost of macrolide-resistant campylobacters reported by the groups of Zhang and Yuan (669)(670)(671). Additional pumps that are independent of CmeABC and CmeEFG also likely mediate MDR (16) but remain to be further studied.…”
Section: Campylobacter Sppmentioning
confidence: 99%
“…Macrolide resistance and associated fitness costs have been reported in Campylobacter jejuni (156,157), and the 23S rRNA mutation A2074C, which confers a high level of macrolide resistance, was associated with a fitness cost in this bacterium (156). Moreover, Zeitouni et al reported in vitro experiments that demonstrated that macrolide resistance imposed a fitness cost; however, a spontaneous mutant that evolved in vivo had a colonization capacity that was similar to that of the susceptible strain (158).…”
Section: Resistance To Macrolides and Effect On Virulencementioning
confidence: 99%